The effects of ultrasonic processing on the antioxidant activity of Geotrichum candidum LG-8 and its cell wall extracts - Jiao, Fengping; Cui, Xianping; Gong, Xiaodi; Jiang, Guozheng; Wang, Jinbiao; Meng, Ling (Frontiers in Nutrition, 2024)
Function of cell wall polysaccharide (EPS) are associated with extraction technics. The present work investigated the application of ultrasound in extracting polysaccharide with antioxidant activity from Geotrichum candidum LG-8 cells, and possible effects of ultrasound on antioxidant activity of LG-8 cells. The conditions for extracting water-soluble EPS were optimized.Ultrasound treatments for 18 min, at pH7.0, with intensity of 40 W/cm 2 and 0.75 M of NaCl solution were selected. The ABTS radical scavenging efficiency of LG-8 cells was improved by 47% after ultrasonic processing. The ultrasonic-extracted LG-EPS1 and LG-EPS3 at 1 mg/mL showed significant ABTS (2,2'-Azinobis-(3-ethylbenzthiazoline-6-sulphonate)) radical scavenging efficiency (26% and 51%). In addition, analysis of monosaccharide components revealed thatLG-EPS1 was composed of mannose and glucose, while LG-EPS3 mainly contained mannose.FTIR spectrum results also showed the presence of polysaccharides. Typical polysaccharide structures (nanoparticles) of LG-EPS1 and LG-EPS3 were observed by SEM. It turned out that, ultrasound was applicable to extract polysaccharide from Geotrichum candidum LG-8, and efficient to improve ABTS radical scavenging ability of the cells. Consequently, Geotrichum candidum LG-8 and its ultrasonic-extracted polysaccharide was excellent nanomaterials for natural antioxidants.